The killer robots! : crash and burn - Gaffin, Sam; Harris, Charles (Actor); Mcgowan, Mike; Lushy Lemming Studios; Leomark Studios (Firm) (De Bary, FL : Lushy Lemming Studios, 2016)
After meeting their end in a mechanized gladiator arena, four robot criminals - Auto, Max, Strobo and Trog are fished out of a junk pile, rebuilt and recruited as mercenaries for a mysterious organization of android adventurers. Although reluctant at first, the mercenaries agree to travel to the planet Vidya, an artificial planet ravaged by a computer virus that has sent its robotic inhabitants into a state of primitive barbarism. Assaulted by all manner of killer machines and robots, the mercenaries must make their way through the tumultuous landscape, activate an inter-dimensional communication device, communicate with otherworldly aliens, and bring about a new age of enlightenment and prosperity for a dystopian galactic civilization.
Originally released as a motion picture in 2016
Sam Gaffin, Charles Harris, Mike McGowan, Samuel Williams, Char Calaquian, Jenna Hellmuth, Andy Jones, Grace Kreeger, Mandaddy, Brian Manowitz, Shawn C. Phillips, John Schumann, Tim Wiley.
Editing and music, Sam Gaffin.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 8, 2017).
Keywords: Science fiction films; Action and adventure films; Internet videos; Streaming video